The Pattern of Herbivorous Fish Assemblages in The In Western and Eastern Outermost Island Indonesia - Risandi Dwirama Putra; Rikoh Manogar Siringoringo; Muhammad Abrar; Ni Wayan Purnamasari; Agung Dhamar Syakti (Journal Omni-Akuatika, 2020)
The herbivorous fishes have been considered as a critical functional group and have capability maintaining coral reef resilience and avoiding coral-algal phase-shifts. The present condition shown, almost in tropical reef location, alga has dominated coral, even in the small outer island. The requirement to conduct comprehensive basic research in studying the patterns and composition of herbivorous fish, especially on the small outer islands. Twelve coral reef sites in eastern Indonesia (Liki Islands) and western Indonesia (Natuna Island) used as a research location for comparing the structure patterns of herbivorous fish communities (diversity, density, and body size) using the Underwater Visual Census (UVC) method. There was different pattern of herbivorous fishes families in Liki Island and Natuna Islands, where Acanthuridae is dominant in eastern Indonesia (Liki Islands), including Ctenochaetus striatus (41,00 ± 11,72 se) individuals/350m2, A. maculiceps (23,33 ± 13,61 se) individuals/350m2, Naso hexacanthus (18,67 ± 6,34 se) individuals/350m2 while Scaridae is dominant in western Indonesia (Natuna island), including Scarus rivulatus (31,67 ± 10,61 se) individuals/350m2, Chlorurus sordidus (30,00 ± 8,52 se) individuals/350m2 and Scarus quoyi (19,00 ± 9,73 se) individuals/350m2. Based on herbivore fishes composition Liki Island has a higher density and biomass compared to Natuna Island.Keywords: herbivore, fish, coral, small outer island, Indonesia